A comparison of the performance of microsatellite and methylation urine analysis for predicting the recurrence of urothelial cell carcinoma, and definition of a set of markers by Bayesian network analysis. - Rouprêt, M; Hupertan, V; Yates, DR; Comperat, E; Catto, J; Meuth, M; Lackmichi, A; Ricci, S; Lacave, R; Gattegno, B; Richard, F; Hamdy, F; et al. (2008)
OBJECTIVE: To compare the potential of two diagnostic methods for detecting recurrence of urothelial cell carcinoma (UCC) of the bladder, by (i) detecting alterations in microsatellite DNA markers and loss of heterozygosity (LOH), and (ii) detecting aberrant gene hypermethylation, as UCC has a high recurrence rate in the urinary tract and the disease can invade muscle if new tumours are overlooked. PATIENTS AND METHODS: Over 1 year, urine samples were retrieved from 40 patients already diagnosed with bladder UCC (30 pTa, two pTis, eight pT1). Samples were collected 6 months after bladder tumour resection, during the follow-up schedule. We used samples to analyse nine microsatellite markers and the methylation status of 11 gene promoters. Receiver operating characteristic curves were generated and Bayesian statistics used to create an interaction network between recurrence and the biomarkers. RESULTS: During the study, 15 of the 40 patients (38%) had a tumour recurrence and 14 were identified by cystoscopy (reference method). Overall, microsatellite markers (area under curve, AUC 0.819, 95% confidence interval, CI, 0.677-0.961) had better performance characteristics than promoter hypermethylation (AUC 0.448, 0.259-0.637) for detecting recurrence. A marker panel of IFNA, MBP, ACTBP2, D9S162 and of RASSF1A, and WIF1 generated a higher diagnostic accuracy of 86% (AUC 0.92, 0.772-0.981). CONCLUSION: Microsatellite markers have better performance characteristics than promoter hypermethylation for detecting UCC recurrence. These data support the further development of a combination of only six markers from both methods in urinary DNA. Once validated, it could be used routinely during the follow-up for the early detection and surveillance of UCC from the lower and upper urinary tract.